Interprofessional education about patient decision support in specialty care - Politi, Mary C.; Pieterse, Arwen H.; Truant, Tracy; Borkhoff, Cornelia; Jha, Vikram; Kuhl, Laura; Nicolai, Jennifer; Goss, Claudia (Journal of interprofessional care, 2011)
Specialty care involves services provided by health professionals who focus on treating diseases affecting one body system. In contrast to primary care - aimed at providing continuous, comprehensive care - specialty care often involves intermittent episodes of care focused around specific medical conditions. In addition, it typically includes multiple providers who have unique areas of expertise that are important in supporting patients’ care. Interprofessional care involves multiple professionals from different disciplines collaborating to provide an integrated approach to patient care. For patients to experience continuity of care across interprofessional providers, providers need to communicate and maintain a shared sense of responsibility to their patients. In this article, we describe challenges inherent in providing interprofessional patient decision support in specialty care. We propose ways for providers to engage in interprofessional decision support and discuss promising approaches to teaching an interprofessional decision support to specialty care providers. Additional evaluation and empirical research are required before further recommendations can be made about education for interprofessional decision support in specialty care.